Mathematics and geometry towards ideality in «Domus»’s ideal houses (Lebenswelt. Aesthetics and philosophy of experience., 2018)
Between 1942 and 1943 the editor of the journal «Domus» invited the most important Italian architects to design their ideal houses: fifteen projects designed by seventeen architects were published. They are most instructive to try to understand, firstly, what the philosophical notion of ideal means and, secondly, why mathematical and geometric tools are extensively used to work on ideality, namely, to design ideal houses. The first part of the article focuses on the philosophical foundations of ideality and, after an overview of the fifteen projects, on the use of the golden ratio in two particularly meaningful cases. The second part of the article focuses on the cases in which there is a hidden use of the golden ratio, on the use of the modulus and on the use of the number 2.